"Ghostly Imprints": Revisiting the Tradition of the Death Mask in Digital Clay - Stewart, Michelle (Arts Research Africa, 2022)
This paper explores the representation of the dead through a creative project that involves 3D digital sculptures inspired by forensic facial photographs of unclaimed deceased in government morgues as well as posthumous photographs of the author’s mother-in-law. The project draws on the tradition of death masks and aims to create final portraits that commemorate the individuals and acknowledge the transcendental aspects of death masks. The author’s work is situated within the discourse of art theory and history, rather than forensic art, and emphasises the artistic and conceptual nature of the sculptures. The project is associated with the International Committee of the Red Cross’s Missing and Deceased Migrant Project and explores the humanitarian implications of migrant deaths in South Africa. The paper also delves into the history and evolution of death masks in Western culture, highlighting their significance as representations of true faces and their use in phrenology.